2019
DOI: 10.21608/jppp.2019.40936
|View full text |Cite
|
Sign up to set email alerts
|

Improved the Shelf Life of Guava Fruits by Salicylic Acid against Postharvest Black Spot Disease

Abstract: Guava fruit (Psidium guajava L.) is one of the most important popular fruits in the tropical and subtropical zones. It is a perishable and has a short postharvest shelf life at environment temperature due to climacteric ripening with changes in physicochemical properties; However, the most serious microorganisms attacked guava fruits are the fungi. Guava black spot (GBS) is a latent infection disease caused by the ascomycete fungal Phyllosticta capitalensis, that infect immature guava in the field. This postha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Similarly, Razavi et al (2018) concluded that treating peaches with SA during storage at 1 °C for 4 weeks delayed fruit postharvest decay due to the rising of antioxidant enzymes (APX, SOD, and CAT) content. Similar findings were reported on treating fruit (tomato, apricot, mandarin and guava) with SA during storage, resulted in delayed ripening, decreased decay percentage, extended fruit storage and enhanced fruit quality and storability (El-Abbasy et al, 2018, Orabi et al, 2018, Arafat, 2019. That could be attributed to SA inhibits the action of ethylene receptors, which enhances fruit decay (Heydari et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, Razavi et al (2018) concluded that treating peaches with SA during storage at 1 °C for 4 weeks delayed fruit postharvest decay due to the rising of antioxidant enzymes (APX, SOD, and CAT) content. Similar findings were reported on treating fruit (tomato, apricot, mandarin and guava) with SA during storage, resulted in delayed ripening, decreased decay percentage, extended fruit storage and enhanced fruit quality and storability (El-Abbasy et al, 2018, Orabi et al, 2018, Arafat, 2019. That could be attributed to SA inhibits the action of ethylene receptors, which enhances fruit decay (Heydari et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Salicylic acid is one of the safe natural chemicals used for postharvest quality maintenance of horticultural and ornamental produces, regulates plant growth and development, and affects postharvest physiological and metabolism of perishable crops (Davies, 2010 andArafat, 2019). Aspirin (AS), a trading name for acetylsalicylic acid, undergoes spontaneous hydrolysis to SA, in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%